Truth, Lies, and Concealment: St. Augustine on Mendacious Political Thought. Issue 3 (4th July 2017) - Russell, Jeremiah; Promisel, Michael
Abstract: There is disagreement among scholars regarding the mendacity of esoteric writing. Some see it as a necessarily dishonest mode of communication; others argue it does not meet the conditions of lying; others are more nuanced in their assessment. In this article, we seek to resolve this disagreement by offering a systematic analysis of the literary practice in which we argue that there are both truthful and mendacious forms of esoteric writing. In sum, if an author conceals truths from a general audience while still being truthful on the surface of the text or makes it clear that he is being untruthful, he is not lying; yet if an author conceals truths while intentionally being untruthful on the surface, he is lying. Given the parallel ethical structure between esoteric writing and political discourse, we argue that the analysis provided in this article may illuminate the ethical choices made in both written and political statements.